School for hearig parents of deaf children from a systemic perspective - Uribe Ybañez, Patricia (2001)
Throughout its vital cycle the family is exposed to critical situations which menace its stability. Handling and outcoming this crisis depend on a series of factors which form the family CONTEXT (parents personal data, influence of source families, personality, instruction, etc.). Critical situations must not be assumed as negative ones but as circumstance that give people the opportunity to discover or rediscover their resource ad adaptation ability. A systemic perspective for a School of normal parents with deaf children is presented.